Factorisation and Labeling in Hypergraphs - et. al., C.S. Harisha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Graphs have lots of applications in various domains. They support only pair wise relationships. Hypergraphs does more than graphs. In graph theory, a graph where an edge can join any number of vertices is called as the hyper graph. The corresponding edges are called as hyper edges. The integers used for assignment of labels to the edges and vertices or to only vertices of a graph or to only the edges is called as the graph labeling in this paper we study about factorization and labeling in hyper graphs with the hyper graphs obtained from graphs.